The multidimensionality of social wellbeing: interactions from the individual to the collective level in large cities - Martínez-Martínez, Oscar A.; Ramírez-López, Araceli; Hernández Martínez, Eduardo Gamaliel; Mac Kinney Romero, René (Frontiers in Sociology, 2023)
This paper responds to two questions —What dimensions and indicators are relevant to the construction of social well-being? How are the levels of well-being distributed in the municipalities of Mexico City? To answer these questions, we use data from the Well-being Survey (N= 2871) that is representative of Mexico City and its municipalities. We employed two methods, DM-R distances, and Mamdani’s Fuzzy Inference Method. The results show that all the proposed dimensions and indicators contributed to the building of multidimensional social well-being; in the case of some indicators (social security, built environment, and public insecurity) they contributed less. This suggests government interventions should be designed in order to improve the gaps in those areas. The evidence also indicates that community well-being is a relevant dimension when measuring social well-being in large cities, in addition to identifying areas of intervention for the development of more efficient and inclusive public policies.